Evaluating the forest road systems subjected to different loadings by using the Finite Element Method - MUȘAT Elena Camelia (Forests, 2022)
In the actual context, in which there is a trend of increasing the weight of the vehicles used to transport materials, checking the deformations of road systems as a response to dynamic and static loadings is necessary to better manage the road infrastructure. The goal of the study was to evaluate how the number and the thickness of layers, and the material types could influence the behavior of the road systems subjected to different loads, and to find out which of the road systems have the smallest deformations. The Romania forest roads are classified into three categories, and the most important are the principal forest roads. There were chosen road systems proper to this category. Consequently, nine types of road systems were considered, based on the materials used and the thickness of the layers, and the deformations were evaluated by considering loads of 25, 35 and 45 tons. For modeling the behavior of road systems under different loads, the Finite Element Method (FEM) was used taking into consideration the static domain. The models show that, in all the cases, the deformations depend on the number of layers, while the thickness of the ballast layer can reduce the deformations because of the rigidness of the structure. Those findings are very important because not all the modeled roads systems could provide suitable bearing capacity. Hence, an inappropriate thickness of the layers could negatively influence the behavior of road systems under the traffic with weight increased.
Keywords: forest roads; finite element method; road structure; loadings; truck; wood transport